"Marked" Bodies, Medical Intervention, and Courageous Humility: Spiritual Identity Formation in Nathaniel Hawthorne's The Birthmark. Issue 5 (21st November 2022) - Dow, Keith
Abstract: Nathaniel Hawthorne's The Birthmark offers a sharp lens through which to examine power, purity, and personal identity. Scientist and spiritual idealist, Aylmer, is obsessed with "correcting" the only flaw he perceives in his wife Georgina, the imprint of a small red hand on her pale cheek. For Alymer, this one "imperfection" reaches deep into Georgina's heart, a sign of sin, decay, and mortality. It is the natural that must be overcome with science. Drawing on Hawthorne's tragic fiction, this paper questions the influence of stigma, power dynamics, and mind-body dualism in constructing disability identity within the framework of medical and spiritual practices of care. Whether in the role of a spiritual leader, chaplain, or medical professional, people providing care must first address ableism and perceptions of normalcy in relation to their own identity and calling before offering professional advice to disabled people seeking guidance or support. It is only as professional fields adopt a posture marked by courageous humility that healing practices will promote the flourishing of all people, including those with disabilities.